Metode Dakwah Abdullah Bin Alawi Al-Haddad dalam Kitab Al-Da‘Wah Al-Tammah wa Al-Tadzkirah Al-‘Ammah dan Kesanya di Jawa Timur, Indonesia: The method of propagation of Abdullah Bin Alawi Al-Haddad in the book Al-Da‘wah Al-Tammah wa Al-Tadzkirah Al-‘Ammah and its impact in East Java, Indonesia - Sadili, Imam; Zedan, Asyraf M. (Al-Basirah Journal, 2021)
Abdullah bin Alawi Al-Haddad (1044 H.) is reference figure in Hadramaut, Yemen. His contribution to Islamic da’wah, especially in Indoneisa is very large, that is proven by many of habaib (descendants of the prophet) who have come to Indonesia from Hadramaut, Yemen for da’wah purpose. According to several studies, they are offspring of Abdullah bin Alawi Al-Haddad who lived in Indonesia and becomes permanent residents. Some studies also explain that their da’wah well received by the Indonesian people, therefore this research is important. The research talk about Abdullah’s bin Alawi da’wah methods in his book which is entitled “al-Dakwah At-tammah wa Tadzkirah Ammah” and its impact in East Java. The research results found that Abdullan bin Alawi emphasizes in his book on sosial status condition of da’wa object in line with concept hikmah, mauidzah hasanah da’wah methods in surah AlNahl verse 125. Furthemore, researcher found an effect Abdullah’s bin alawi da’wa method in his book by a lot of Islamic students at Islamic boarding schools in East Java who studied it and it become reference Islamic’s boarding schools alumni to start da’wah activities in the community.